The Effect of Service Quality And Facilities on Customer Satisfaction at Benteng Buah Naga Café & Resto - Kanom, Kanom; Adi Wijaya, Jemi Cahya; Ningsih, Dian Tri Agustin (Ann Publisher, 2024)
Customer satisfaction is where customers' needs, desires, and expectations can be fulfilled, leading to repeat purchases or continued loyalty. Consumers will be more satisfied with the more fulfilled expectations from consumers. This study analyzed the factors influencing customer satisfaction at the Benteng Buah Naga Café & Resto. The variables examined in this study are service quality and facilities, which are thought to impact customer satisfaction. The research approach uses a quantitative approach. The analysis technique used is multiple linear regression analysis with the help of SPSS version 24 (twenty-four). The results showed that the service quality variable positively and significantly affected (t value> ttable, 3,599 > 2.012) customer satisfaction at the Benteng Buah Naga Cafe & Resto. The Facilities variable positively and significantly affects (t value> t table, 2,230 > 2.012) customer satisfaction at the Benteng Buah Naga Cafe & Resto. Simultaneously, service quality and facilities affect customer satisfaction (Fcount> Ftable of 34,483 > 3,20) at the Benteng Buah Naga Café & Resto.